PERLINDUNGAN HUKUM TERHADAP NOTARIS ATAS DUGAAN TINDAK PIDANA PASCA BERLAKUNYA PERATURAN MENTERI HUKUM DAN HAK ASASI MANUSIA NOMOR 7 TAHUN 2016 TENTANG MAJELIS KEHORMATAN NOTARIS - Ratna Nova Andana; Hari Purwadi (Jurnal Repertorium, 2018)
AbstractThis study aims to determine the criteria used by the Honorary Council of Notaries in giving approval or rejection of the Notary's examination by the Investigator. This research is sociological research. Data analysis was done qualitatively with interactive model analysis technique. The results of the research indicate that the main criteria of approval of the notary examination is the fulfillment of the provisions of Article 26 and Article 27 of the Regulation of the Minister of Justice and Human Rights Number 7 of 2016 concerning the Notary Publicity Council, the Notary has performed his duty and position correctly in order to assist the ongoing judicial process or when the Notary does not meet the inspection call by the Examining Assembly. Approval of the examination of a Notary will be rejected if the offense is not the domain of the Notary Publicity Council, the non-fulfillment of the provisions of Article 26 and Article 27 of the Regulation of the Minister of Justice and Human Rights Number 7 of 2016 concerning the Notary Publicity Board or because the Notary has performed his duties and positions correctly.Keywords: legal protection; Notaries; alleged offenses; Honorary Council of NotariesAsbtrak Penelitian ini bertujuan untuk mengetahui kriteria yang digunakan oleh Majelis Kehormatan Notaris dalam memberikan persetujuan maupun penolakan pemeriksaan Notaris oleh Penyidik. Penelitian ini adalah penelitian sosiologis. Analisis data dilakukan secara kualitatif dengan teknik analisis model interaktif. Hasil penelitian menunjukkan bahwa kriteria utama pemberian persetujuan pemeriksaan Notaris adalah terpenuhinya ketentuan Pasal 26 dan Pasal 27 Peraturan Menteri Hukum dan Hak Asasi Manusia Nomor 7 Tahun 2016 tentang Majelis Kehormatan Notaris, Notaris telah melaksanakan tugas dan jabatannya dengan benar dalam rangka membantu proses peradilan yang sedang berlangsung atau pada saat Notaris tidak memenuhi panggilan pemeriksaan oleh Majelis Pemeriksa. Persetujuan pemeriksaan Notaris akan ditolak apabila tindak pidana yang dimaksud bukan merupakan ranah Majelis Kehormatan Notaris, tidak terpenuhinya ketentuan Pasal 26 dan Pasal 27 Peraturan Menteri Hukum dan Hak Asasi Manusia Nomor 7 Tahun 2016 tentang Majelis Kehormatan Notaris atau karena Notaris telah melaksanakan tugas dan jabatannya dengan benar.Kata Kunci: perlindungan hukum; Notaris; dugaan tindak pidana; Majelis Kehormatan Notaris